Gestão estadual da atenção básica: características do processo de trabalho de uma Diretoria Regional de Saúde da Bahia, 2010 - Andrade , Liane Santiago (2011)
Brazilian federalism has caused, over time, the structuring of institutional arrangements that encompassed the functions of government to the needs of the population. The revaluation of the role of state health departments and the regionalization process triggered mainly with the Operational Health Care (NOAS) and the Pact of management that led to a restructuring of health policy in several states. In Bahia, in the case of the current State Policy of primary care, highlighting the strengthening component of the loco - regional organizational redesign reflects an appreciation of the Regional Health Directories (DIRES), changing the relationship between municipal and state level, similar to the cooperative regionalization proposed by the Health Agreement (BAHIAb, 2008). This study aimed to examine the management of primary care within a regional board of health department of the state of Bahia in 2010. Theoretically the practice of management to the Theory of Macroorganização and the Labour Process. The study is qualitative, case study. The techniques of data collection were the systematic observation, the semi-structured interviews and documentary analysis. The research subjects are managers and technical representatives from three primary levels of management. The state level is the regional focus of the study with five representatives. The others were entered as key informants. The results were organized into two articles, one dealing with the work process itself and the other addressing the characteristics of primary health care management in the light of DIRES Iron Triangle of Carlos Matus (1996). In Article 1, the results show that the investments made so far for the reformulation of the model management DIRES are still insufficient for a change of organizational culture rooted in a functional-bureaucratic model adopted by the state, reflecting a performance still fragmented, uncoordinated and dependent. The support from the central level imposed by a proposal for continuing education has contributed to the reflection of this work. In Article 2, the analysis of the Iron Triangle revealed a low liability management, with a predominance of emergencies and improvisations. There are a limited collection on accountability for performance and a predominance of a more routine in solving problems (little innovation and creativity). Responsibility was presented as the apex more fragile. The strongest was the Directionality, which may be associated with the implementation process of the State Politics of Primary Care, through institutional support and continuing education. Despite improvements highlighted in the decentralization of some actions for the management of primary care in DIRES studied for a strong centralization of some decisions. The great shift to take account of a historical gap of regional governance requires breaking the barriers of political territories, reconfiguring and investing in regional management for a strong, independent, articulate and cohesive with the purposes of state health policy in line with the specificities of each region.